2013
DOI: 10.1002/pssb.201200976
|View full text |Cite
|
Sign up to set email alerts
|

Novel mechanism of damage introduction into carbon nanotubes caused by irradiation in gas medium

Abstract: In situ measurements of the resistance changes of carbon nanotube bundles irradiated by 60 Co g-quanta at room temperature are presented. The peculiarity of our study consists in providing the sample irradiation in a hermetic cell filled with different gases at atmosphere pressure. Here we demonstrate the results for irradiation in hydrogen, deuterium, helium and argon media. The obtained dependences of the resistance change versus irradiation dose in vacuum are presented, too. We have developed a novel two-st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Danilchenko et al also reported the introduction of defects into CNTs by irradiation [30] while other groups have exploited these effects to functionalize the surfaces of CNTs. [31].…”
Section: Introductionmentioning
confidence: 99%
“…Danilchenko et al also reported the introduction of defects into CNTs by irradiation [30] while other groups have exploited these effects to functionalize the surfaces of CNTs. [31].…”
Section: Introductionmentioning
confidence: 99%
“…These irradiation conditions were chosen for several reasons:  -irradiation introduces structural defects, mostly vacancies [25], and the efficiency of defect creation depends strongly on the surrounding gas medium during  -irradiation [26]. Moreover,  -irradiation up to a dose of 1.7x10…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, we report experimental results for the change in conductivity of SWCNT bundles when irradiated with 60 Co γ -rays in hydrogen and deuterium media as well as in vacuum. These irradiation conditions were chosen for several reasons: γ -irradiation introduces structural defects, mostly vacancies [25], and the efficiency of defect creation depends strongly on the surrounding gas medium during γ -irradiation [26]. Moreover, γ -irradiation up to a dose of 1.7 × 10 7 rad in hydrogen leads to the accumulation of atomic hydrogen inside SWCNTs, with a concentration of up to 3.5 at.% [10].…”
Section: Introductionmentioning
confidence: 99%